What Does Unexpected Suboptimal Response During Ovarian Stimulation Suggest, an Overlooked Group? - Wang, Bijun; Liu, Wenxia; Liu, Yi; Zhang, Wen; Ren, Chenchen; Guan, Yichun (Frontiers in Endocrinology, 2021)
Unlike poor ovarian response, many patients respond “suboptimally” to ovarian stimulation despite being predicted to be normal responders based on their ovarian reserve markers. Even though we can improve the number of retrieved oocytes by increasing rFSH dose and adding LH, the effect of suboptimal ovarian response on cumulative live birth rate (CLBR) and offspring safety is unclear. This study focuses on the unexpected suboptimal response during ovulation induction, and its causes and outcomes are analysed, for the first time with a large amount of data used to compare the cumulative pregnancy rate (CPR), CLBR and offspring safety of patients with one complete ART cycle with all embryos used. Our analysis included 5261 patients treated with the GnRH agonist long protocol for their first IVF–embryo transfer (ET) cycles. Patients were divided into two groups according to whether the ovarian response was suboptimal. Propensity score matching (PSM) was utilized for sampling at up to 1:1 nearest-neighbour matching with calipers to balance the baseline and improve comparability between groups. Age，BMI and basal FSH were independent risk factors for slow response, and initial dosage of Gn, FSH on the first day of Gn, and LH on the first day of Gn were independent protective factors for suboptimal response. Suboptimal responders were also more likely to have irregular menses. Regarding the clinical pregnancy rate of the fresh IVF/ICSI-ET cycles, adjusted results of the two groups were not significantly different. No difference in the CPR, CLBR, or offspring safety related data such as gestational age, preterm delivery, birthweight,Birth-height and Apgar Scores between the two groups after PSM. Age-related changes in the number of oocytes retrieved from women aged 20–40 years between the two groups were different, indicating that suboptimal response in elderly patients suggests a decline in ovarian reserve. Although we can now improve the outcome of suboptimal responders，it increases the cost to the patients and the time to live birth, which still needs our attention.